2019
DOI: 10.1242/dev.172361
|View full text |Cite
|
Sign up to set email alerts
|

Kidney micro-organoids in suspension culture as a scalable source of human pluripotent stem cell-derived kidney cells

Abstract: Kidney organoids have potential uses in disease modelling, drug screening and regenerative medicine. However, novel cost-effective techniques are needed to enable scaled-up production of kidney cell types in vitro. We describe here a modified suspension culture method for the generation of kidney micro-organoids from human pluripotent stem cells. Optimisation of differentiation conditions allowed the formation of micro-organoids, each containing six to ten nephrons that were surrounded by endothelial and strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 33 publications
2
139
0
Order By: Relevance
“…RNA sequencing analysis indicated that Takasato organoids were very similar to the first trimester kidney . Several studies utilized the Takasato protocol to conduct developmental studies (Bantounas et al, 2018), disease modeling (Forbes et al, 2018), in vivo transplantation (Koning et al, 2018), and a scale-up of organoid generation (Kumar et al, 2019). Another study was conducted by Bonventre's laboratory.…”
Section: Kidney Organoid Differentiation Protocols and Methodsmentioning
confidence: 99%
“…RNA sequencing analysis indicated that Takasato organoids were very similar to the first trimester kidney . Several studies utilized the Takasato protocol to conduct developmental studies (Bantounas et al, 2018), disease modeling (Forbes et al, 2018), in vivo transplantation (Koning et al, 2018), and a scale-up of organoid generation (Kumar et al, 2019). Another study was conducted by Bonventre's laboratory.…”
Section: Kidney Organoid Differentiation Protocols and Methodsmentioning
confidence: 99%
“…In these cultures, typical proximal tubule cell characteristics have been demonstrated, such as albumin uptake, expression of tight junction proteins, expression of OAT1, microvilli, and apical and basolateral membrane polarization. In addition, cytotoxicity was demonstrated using cisplatin (Czerniecki et al 2018;Freedman et al 2015;Kaminski Michael et al 2016;Morizane et al 2015;Takasato et al 2015), gentamicin (Freedman et al 2015;Kaminski Michael et al 2016;Morizane et al 2015), tacrolimus (Kaminski Michael et al 2016), and adriamycin (Kumar et al 2019). As earlier stated, kidney tubuloids grown from adult stem cells (ASCs) are another promising approach as they allow for long-term culturing and better maturation without losing chromosomal stability (Schutgens et al 2019).…”
Section: Perspectives In In Vitro Models' Developmentmentioning
confidence: 98%
“…Indeed, with time in culture the center of organoids show deposition of extracellular matrix and a decline in endothelial populations . Several approaches to generating kidney organoids in suspension show clear evidence of cyst formation and fibrotic expansion with time (Przepiorski et al 2018;Kumar et al 2019). This suggests that while we have managed to replicate early patterning events, we have not created an environment suitable for tubular proliferation and continued development.…”
Section: Relative Maturation Of Kidney Organoidsmentioning
confidence: 99%
“…What is possible outside of the embryo is to modify culture format to optimize such models for one or other application, even when this does not necessarily involve creating a perfect model of the developing organ. A variety of studies have now claimed improvements in scale up or relative maturation, including the use of dis-tinct culture formats and changes in culture materials (Table 2; Cruz et al 2017;Czerniecki et al 2018;Przepiorski et al 2018;Garreta et al 2019;Gupta et al 2019;Kumar et al 2019). In addition, protocols for the generation of specific renal cell subtypes, such as podocyte or collecting duct epithelium, are being reported (Musah et al 2017;Taguchi and Nishinakamura 2017;Hale et al 2018;Yoshimura et al 2019).…”
Section: Other Points Of Divergence Between Developing Organ and Orgamentioning
confidence: 99%
See 1 more Smart Citation